Continuity of Islamic Educational Institutions - Iffatul Aimmah; Muhtadi Abdul Mun’im (COMPETITIVE: Journal of Education, 2024)
Islamic educational institutions have developed from time to time. This is so that Islamic educational institutions can be present to answer the challenges of the times. This research will discuss continuity in Islamic educational institutions. The research method used in this education is qualitative literature study. The results of this study show that continuity in Islamic educational institutions in accordance with their main objectives can be done by developing curriculum, improving the quality of teaching staff, utilization with technology and holding cooperation with other institutions.